Global solutions of a two-dimensional initial boundary-value problem for a system of semilinear magnetoelasticity equations - Botsenyuk, А. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove the theorem on the existence and uniqueness of global solutions of a system of semilinear magnetoelasticity equations in a two-dimensional space.